ANTIBIOTIC SUSCEPTIBILITY TEST TOWARDS COCKROACH (PERIPLANETA AMERICANA) FOOT BACTERIA IN THE NUTRITION DEPARTMENT AREA OF PALU CITY HOSPITAL - I Nengah Nengah Kundera; Yulia Windarsih; Abd. Rauf (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Cockroaches (Periplaneta americana) are known to have potential as vectors of various pathogenic bacteria in various locations including the nutrition department area in the hospitals. Research related to the role of these animals as vectors of pathogenic bacteria has not been done. The provision of food in the hospital nutrition department has the potential for bacterial contamination from food, equipment, hospital staff, and the environment. Cockroaches can be a vector for spreading various nosocomial infectious diseases in hospitals. A descriptive method was used, and the data were obtained by bacterial isolation, Gram staining method, antibiotic sensitivity test, and bacterial identification using Microbact system software 2000. This study was carried out at the Biology Education Laboratory, Education and Teacher Training Faculty,  Tadulako University. Based on the results of the study, 6 species of bacterial isolates from cockroach feet   in the nutrition department area of Palu city hospital, namely E. coli, S. arizonae, Salmonella sp., K. ozaenae, S. simulans, and S. enterica. Antibiotic sensitivity test showed that four bacteria exhibited multi-drug resistance to antibiotics Amoxycillin, Chloramphenicol and Vancomycin. Meanwhile,S. enterica was still sensitive to the five tested antibiotics namely Amoxycillin, Chloramphenicol, Ciprofloxacin, Ofloxacin, and Vancomycin. serious policies and handling are needed to control new types of vectors that carry diseases in humans.. meanwhile,S. entericawas still sensitive to the five tested antibiotics.